Baseball Myths: Debating, Debunking, and Disproving Tales from the Diamond - Deane, Bill (Rowman & Littlefield Publishers, 2012)
Baseball followers have been perpetuating, debating, and debunking myths for nearly two centuries, producing a treasury of baseball stories and “facts.” Yet never before have these elements of baseball history been carefully scrutinized and compiled into one comprehensive work—until now. In Baseball Myths: Debating, Debunking, and Disproving Tales from the Diamond, award-winning researcher Bill Deane examines baseball legends—old and new. This book covers such legendary players as Shoeless Joe Jackson, Ty Cobb, Babe Ruth, Joe DiMaggio, Jackie Robinson, Pete Rose, and Derek Jeter, while also looking at lesser-known figures like Dummy Hoy, Grover Land, Wally Pipp, and Babe Herman—not to mention people who found fame in other fields, such as Civil War General Abner Doubleday, Cuban dictator Fidel Castro, and comedians Bud Abbott and Lou Costello. Deane’s original research and logic will educate, amuse, and often surprise readers, revealing the truth behind such legends as the inventor of baseball, the first black player in the major leagues, and even the origin of the hot dog. With photographs, stats, and more than 80 myths examined, this book is sure to fascinate everyone, from the casual baseball fan to lifelong devotees of the sport.